Muscle Fatigue in the Temporal and Masseter Muscles in Patients with Temporomandibular Dysfunction. (26th March 2015) - Woźniak, Krzysztof; Lipski, Mariusz; Lichota, Damian; Szyszka-Sommerfeld, Liliana
Abstract : The aim of this study is to evaluate muscle fatigue in the temporal and masseter muscles in patients with temporomandibular dysfunction (TMD). Two hundred volunteers aged 19.3 to 27.8 years (mean 21.50, SD 0.97) participated in this study. Electromyographical (EMG) recordings were performed using a DAB-Bluetooth Instrument (Zebris Medical GmbH, Germany). Muscle fatigue was evaluated on the basis of a maximum effort test. The test was performed during a 10-second maximum isometric contraction (MVC) of the jaws. An analysis of changes in the mean power frequency of the two pairs of temporal and masseter muscles (MPF%) revealed significant differences in the groups of patients with varying degrees of temporomandibular disorders according to Di (P < 0.0000 ). The study showed an increase in the muscle fatigue of the temporal and masseter muscles correlated with the intensity of temporomandibular dysfunction symptoms in patients. The use of surface electromyography in assessing muscle fatigue is an excellent diagnostic tool for identifying patients with temporomandibular dysfunction.